American evangelicals: a contemporary history of a mainstream religious movement - Hankins, Barry (Critical issues in history, 2008)
Awakening and the beginning of American evengelicalism -- The struggle with modernism : origins of the culture wars -- Battling with science : from antievolution to the intelligent design -- Millennialism : folk religion and the career of end-times prophecy -- Considering equality : the tradition of gender, race, and gay rights -- Inspired politics : evangelical religion in the political marketplace -- Back to the academy : evangelical scholars and the American mind